2020
DOI: 10.1097/j.pain.0000000000002030
|View full text |Cite
|
Sign up to set email alerts
|

The α2/α3GABAA receptor modulator TPA023B alleviates not only the sensory but also the tonic affective component of chronic pain in mice

Abstract: Diminished synaptic inhibition in the spinal dorsal horn is a major contributor to pathological pain syndromes of neuropathic or inflammatory origin. Drugs that enhance the activity of dorsal horn 2/3GABAARs normalize exaggerated nociceptive responses in rodents with neuropathic nerve lesions or peripheral inflammation but lack most of the typical side effects of less specific GABAergic drugs. It is however still unknown whether such drugs also reduce the clinically more relevant conscious perception of pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In addition, GSEA supported that gene sets with statistical signi cance were mostly related to immune responses. Conforming to this work, previous studies con rmed that SNI was highly associated with in ammation (38,39). Immunocytes, including lymphocytes, resident cells, neutrophils, and macrophages, can produce various chemical molecules, including purines, lipids, histamine, protons, bradykinin, serotonin, chemokines, cytokines, nerve growth factors in the process of in ammation (40).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, GSEA supported that gene sets with statistical signi cance were mostly related to immune responses. Conforming to this work, previous studies con rmed that SNI was highly associated with in ammation (38,39). Immunocytes, including lymphocytes, resident cells, neutrophils, and macrophages, can produce various chemical molecules, including purines, lipids, histamine, protons, bradykinin, serotonin, chemokines, cytokines, nerve growth factors in the process of in ammation (40).…”
Section: Discussionsupporting
confidence: 76%
“…22 The automated squint assay was validated using a well-known pain trigger, formalin, which has been reported to induce grimace. 18 We then compared automated measurements with manual measurements of grimace and orbital tightening in response to the neuropeptide calcitonin gene-related peptide (CGRP), which is known to cause squinting and other components of grimace in mice. 22 Finally, the automated assay was used to test the CGRP-related peptide amylin, which has recently been shown to induce migraine in patients and migraine-like symptoms in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no significant clinical analgesic and anti-inflammatory drugs with a GABAergic mechanism of action, recent studies showed that central and periphery GABA A Rs play a major role in nociception and inflammation. Considerable evidence supported that facilitating GABAergic inhibition was able to reverse pathological pain states in mice and also pointed to the associations between GABA A R and inflammatory disorders in brain and peripheral organs; GABA was able to decrease the proinflammatory mediator production and ameliorate inflammatory symptom (Knabl et al, 2008;Munro et al, 2009;Bhat et al, 2010;Seifi et al, 2018;Neumann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…GABA binds to GABA A Rs at the α-β interface, enabling an influx of chloride ions through the central pore, causing receptor hyperpolarization, thus inhibiting neurotransmission ( Lüddens and Korpi, 1995 ; Zhu et al, 2018 ). The genetic approach and pharmacological intervention have been employed to study the GABA/GABA A Rs neurotransmission system ( Fischer, 2017 ; Ge et al, 2019 ; Neumann et al, 2021 ). Many drugs target GABA A Rs, thus affect GABAergic functions.…”
Section: Introductionmentioning
confidence: 99%